(untitled) (Journal on studies and research of academic knowledge, 2017)
Linguistic attitudes are studied from the contact of more than one language because they influence the election of one or an additional language for communication. Consequently, to contribute to a better sociolinguistic understanding of Guaraní Spanish bilingualism in the Paraguay Argentina border, it was explored the variations of the linguistic attitudes of the Guarani and Spanish bilingualism of academics interested in the subject. This study was descriptive, non-experimental with quantitative design. A linguistic questionnaire was applied to collect data, which was also composed with assertive expressions where the informant had the opportunity to state their level of acceptance or rejection of what was being suggested. The attitude concerning Guaraní and Spanish languages was outlined, in overall, as positive, however, Spanish had a superior positive trend compared to Guaraní in the Paraguay-Argentina border regions. When considering the attitudes of Paraguayans and Argentinians, the former revealed higher affection for the Guarani language, a condition assumed by the linguistic reality of Paraguay, where the Guarani language is official along with Spanish and it is also extensively spoken. Whereas the Spanish language, both Paraguayans and Argentinians treasured this language.